Aquisição de livros em bibliotecas universitárias: gestão dos processos da Biblioteca Central da Universidade Federal da Paraíba - Carvalho, Amanda Vieira (2021)
The general objective of this research is to propose improvements to the work process of acquiring books at UFPB, focusing on the activities developed by the Collection Development Division (DDC) of the Central Library, through the techniques of modeling and analysis of business processes (BPM). Thus, we sought to identify and analyze the demands and challenges related to the book purchase process carried out by the UFPB Central Library, through the detailing of its flows, activities, regulations and the parties involved, in order to optimize the process of acquiring books from the Central Library, favoring in general the improvement of the collection's updating. Since the University Library is a structure that supports teaching, research and extension, the quality of its collection affects the performance of the educational institution as a whole, the academic formation of the entire community, in addition to promoting citizenship through equal access to information and knowledge. Furthermore, the relevance of the theme is also highlighted in the context of the National System of Higher Education Assessment (SINAES), given the requirement to adapt the library's book collection to the Pedagogical Course Project (PPC) of undergraduate courses, requiring speed and standardization of the procurement process. The research is classified as descriptive, of an applied nature, with a qualitative approach. As for the technical procedures, this work consists of a case study, which used as data collection techniques the direct observation of the process, document research and interviews with the work team at BC, which centralizes the book purchasing process throughout the University. For the mapping of the workflows, the BPMN notation was used, through the Bizagi Modeler software. And for the analysis and validation, two quality tools were used: the ISO/TR 26122 questionnaire and the Root Cause Analysis through the Fishbone Diagram, which enabled the validation of the mapped process, the identification of its points and 4 opportunities for improvement in the process. In the end, it was possible to redesign the proposal for an improved process, aiming at the speed and standardization of tasks, the development of clear guidelines and the improvement of the existing practice, contributing, in general, to the improvement of the updating of the collection of the Libraries that comprise the UFPB Library System, through the improvement of activities carried out by the sectors responsible for the acquisition of books from this institution.